The six types of nonbelief: a qualitative and quantitative study of type and narrative - Silver, Christopher F.; Coleman, Thomas J.; Hood, Ralph W.; Holcombe, Jenny M. (2014)
Extensive research has been conducted in exploration of the American religious landscape; however, only recently has social science research started to explore nonbelief in any detail. Research on nonbelief has been limited as most research focuses on the popularity of the religious "nones" or the complexities of alternative faith expressions such as spirituality. Through two studies, one qualitative and one quantitative, this research explored how nonbelievers’ self-identify. Study 1 (the qualitative study) discovered that individuals have shared definitional agreement but use different words to describe different types of nonbelief. Through thematic coding, a typology of six different types of nonbelief was observed. Those are Academic Atheists, Activist Atheist/Agnostics, Seeker Agnostics, Antitheists, Non-Theists, and the Ritual Atheists. Study 2 explored the empirical aspects of these types related to the Big Five Domain, Ryff Psychological Well-Being, Narcissistic Personality Inventory, Multidimensional Anger Inventory, Rokeach Dogmatism Scale, and intersections related to religious and spiritual ontology.
Keywords: Agnosticism; Atheism; Nonbelief; Nonreligion; Personality; Secularity; Typology